Functional outcome of Spontaneous Intracerebral Hemorrhage after Conservative Management: A Retrospective Hospital-Based Study - Singh, Sunil; Kafle, Prakash; Chaudhary , Pramod Kumar; Yadav, Dipak Kumar; Joshi, Narendera Prasad (Medical Journal of Eastern Nepal, 2025)
Background Spontaneous intracerebral hemorrhage (ICH) is a critical neurological emergency with high mortality and morbidity. While conservative management is the primary treatment for most patients, functional outcomes are variable. This study assesses these outcomes and their predictors. Methods A retrospective study was conducted at a tertiary care center, including 75 adults with CT-confirmed spontaneous ICH managed conservatively. The primary outcome was functional status at discharge, measured by the Glasgow Outcome Scale (GOS). Results The mean age was 58.5 years. In-hospital mortality was 13.3%. A good recovery (GOS 5) was observed in 30.7% of patients. Older age and delayed presentation were significantly correlated with poorer GOS scores. Pontine hemorrhages were associated with the worst outcomes. Conclusion A significant proportion of patients achieved favorable outcomes with conservative management. Age, time to presentation, and hemorrhage location are critical prognostic factors, underscoring the importance of early and optimized medical care.